No more lies the myth and the reality of American history - Gregory, Dick 1932-2017 (Amistad, an imprint of HarperCollins Publishers, 2021)
"In 1972, during the Black Power Movement, iconoclast Dick Gregory challenged one of the foundations of America itself--its history, which had been written almost exclusively from the white male perspective. In No More Lies, this true trailblazer gave voice to African Americans, speaking their truth about the past and race relations in the United States. No More Lies offers this incomparable satirist's intellectual, conspiratorial, and humorous spin on the facts. No subject is off limits from his critical eye--Gregory examines numerous aspects of culture and history, from the slave trade, police brutality, the wretchedness of working-class life and labor unions to the 1968 Civil Rights Act, the Founding Fathers, "happy slaves," and entrepreneurs. Although this absorbing book is more than forty years old, its provocative truths continue to reverberate in our lives today. With No More Lies, Gregory inspire a new generation to connect what is happening today with what has happened in the past." --Amazon.com
Reprint
Keywords: Geschichte; Rassismus; Ethnische Beziehungen; Schwarze; USA; African Americans / History; United States / History; United States / Race relations; Noirs américains / Histoire; États-Unis / Histoire; États-Unis / Relations raciales; African Americans; Race relations; United States; History